Optimization of cryoprotectants and storage temperatures for preserving viability and probiotic properties of lyophilized bacterial strains from chicken gut. - Dipankar Sardar; Istiaq Morol; Johra Bari; Amalan Sarkar; Adnan Habib (PLoS ONE, 2025)
Probiotics, particularly strains from the genera Bacillus, Lactobacillus, and Staphylococcus, play a vital role in gut health, immune modulation, and pathogen inhibition. However, environmental stressors during storage often compromise their long-term viability and probiotic functionality. By examining how lyophilization affects the viability and probiotic functionality of certain strains of Bacillus, Lactobacillus, and Staphylococcus, this study sought to understand how storage conditions and protective agents affect bacterial survival and important probiotic characteristics. The bacterial strains were isolated from the gastrointestinal tract of native chickens, cultivated in MRS broth, subjected to freeze-drying with different cryoprotectant formulations, and stored at varying temperatures (4°C, -20°C, and -80°C) for up to 12 months. Survival rates, stress resistance under simulated gastric and intestinal conditions, and probiotic functionality were evaluated over time. The results demonstrated that ultra-low temperature storage (-80°C) combined with a formulation of 5% glucose, 5% sucrose, 7% skim milk powder, and 2% glycine provided optimal protection. This combination effectively reduced oxidative and gastrointestinal stress and preserved key probiotic traits, including adhesion potential, antimicrobial activity, and metabolic stability. Conversely, strains stored without cryoprotectants or at higher temperatures exhibited significant viability loss and functional decline. The study highlights the critical role of optimized cryoprotection in maintaining probiotic efficacy during long-term storage. Our findings reinforce the necessity of selecting appropriate excipients and storage conditions to sustain probiotic efficacy, providing valuable insights for the development of stable, high-quality probiotic formulations. Future research should explore strain-specific responses to lyophilization and alternative preservation strategies to improve probiotic stability and performance.